In-vitro investigation of biofilm-specific resistance and virulence of biofilm-forming uropathogenic Escherichia coli - Sara A. Alshaikh; Tarek El-Banna; Fatma Sonbol; Mahmoud H. Farghali (Novel Research in Microbiology Journal, 2024)
Uropathogenic Escherichia coli (UPEC) is the primary etiologic agent of urinary tract infections (UTIs). This study aimed to investigate the difference in antimicrobial susceptibility of UPEC isolates in the planktonic and biofilm states. Important virulence factors were also evaluated. The minimum inhibitory concentrations (MICs) were determined and recorded as 0.5-64 μg/ ml for amikacin, 0.5-64 μg/ ml for cefotaxime, 0.25-64 μg/ ml for cefepime, 0.25-16 μg/ ml for meropenem, and 0.125-32 μg/ ml for ciprofloxacin. Biofilm-specific resistance was assessed using the minimum biofilm eradication concentration (MBEC). The obtained results for MBEC were: 8-512 μg/ ml for amikacin, 32-512 μg/ ml for cefotaxime, 8-512 μg/ ml for cefepime, 4-256 μg/ ml for meropenem, and 4-128 μg/ ml for ciprofloxacin. The virulence factors were evaluated using suitable phenotypic techniques. Our findings revealed a significant enhancement in the antimicrobial resistance after biofilm formation. The MBEC values were higher than the MIC values by 2-128 folds for amikacin, 2-256 folds for cefotaxime, 2-64 folds for cefepime, 8-128 folds for meropenem, and 4-128 folds for ciprofloxacin. The swimming and swarming motilities demonstrated a significant positive correlation (rs = 0.506, P< 0.001). Protease production analysis revealed a large variation, with the weak biofilm-producing isolates EW2 and EW15 displaying the largest zone diameters of 39 mm and 33 mm; respectively. We have also evaluated the distribution and levels of siderophore production, which were significantly associated with meropenem resistance. Finally, this study underscores the importance of considering biofilm formation in UPEC treatment and emphasizes the need for therapeutics targeting these biofilms.